2016
DOI: 10.1108/ijmhsc-09-2015-0033
|View full text |Cite
|
Sign up to set email alerts
|

Somali refugees’ perspectives regarding FGM/C in the US

Abstract: Purpose: To explore perspectives of Somali refugees on FGM/C and potential changes in these after migration. Methods: Qualitative semi-structured interviews were conducted in Denver, Colorado, US, with 13 Somali refugees. Thematic content analysis was used to analyze the data. Findings: Change of perspectives regarding the support of FGM/C were noted among all participants, with most opposing infibulations, FGM/C type III, after migration but supporting Sunna, the cutting of the clitoris, FGM/C type I. Changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…This practice is common in 30 countries in Africa, the Middle East and Asia ( 65 ). The prevalence and practice of female genital mutilation practices in the United States was low and rare ( 66 , 67 ), but the number of those who come to the United States having experienced this in other countries was high ( 66 ). More research is needed in more diverse populations to understand the FGM practices in the United States and their impact on Arab American women's sexual health.…”
Section: Resultsmentioning
confidence: 99%
“…This practice is common in 30 countries in Africa, the Middle East and Asia ( 65 ). The prevalence and practice of female genital mutilation practices in the United States was low and rare ( 66 , 67 ), but the number of those who come to the United States having experienced this in other countries was high ( 66 ). More research is needed in more diverse populations to understand the FGM practices in the United States and their impact on Arab American women's sexual health.…”
Section: Resultsmentioning
confidence: 99%
“…However, in at least two studies, women reported having mixed feelings [60] or felt it was unnecessary to discuss FGM/C with their daughters or in their communities [58]. Furthermore, in four studies, women reported pressure from family members in their country of origin or in the United States to have their daughters undergo FGM/C [31, 32, 37, 61].…”
Section: Resultsmentioning
confidence: 99%
“…In at least 11 studies, women described their understanding of FGM/C as a religious practice (or requirement), a cultural practice, or both [25, 28, 32, 33, 36, 42, 44, 45, 56, 60, 61]. Across studies, regardless of where respondents came from, they more commonly reported that FGM/C is a cultural rather than religious practice.…”
Section: Resultsmentioning
confidence: 99%
“…Being in contact with members of family as well. Yet not to Fatma from Mogadishu, who has traversed half the world to find a better place for herself, from a nation "at a crossroads of extreme poverty, conflict and neglected tropical diseases" (Jaffer & Hotez, 2016), a country where female genital mutilation is a reality (McNeely & Jong, 2016), to Slovenia, where a border fence has been erected to "protect" the citizens from the Other. Fatma's narrative tells us that by many countries' asylum laws, she should be able to enter Europe as an asylum seeker, yet nothing might happen due to the sheer number of refugees and the failing bureaucratic and legal system that tends to hinder, rather than help, more increasingly, as the years go by.…”
Section: Narrativementioning
confidence: 99%